Influence of tides and gravity waves on layering processes in the polar summer mesopause region - P. Hoffmann; M. Rapp; J. Fiedler; R. Latteck (Annales Geophysicae, 2008)
Polar Mesosphere Summer Echoes (PMSE) have been studied at Andenes (69° N, 16° E), Norway, using VHF radar observations since 1994. One remarkable feature of these observations is the fact that {during 50% of the time,} the radar echoes occur in the form of two or more distinct layers. In the case of multiple PMSE layers, statistical analysis shows that the lower layer occurs at a mean height of ~83.4 km, which is almost identical to the mean height of noctilucent clouds (NLC) derived from observation with the ALOMAR Rayleigh/Mie/Raman lidar at the same site. To investigate the layering processes microphysical model simulations under the influence of tidal and gravity waves were performed. In the presence of long period gravity waves, these model investigations predict an enhanced formation of multiple PMSE layer structures, where the lower layer is a consequence of the occurrence of the largest particles at the bottom of the ice cloud. This explains the coincidence of the lowermost PMSE layers and NLC. During periods with enhanced amplitudes of the semidiurnal tide, the observed NLC and PMSE show pronounced tidal structures comparable to the results of corresponding microphysical simulations. At periods with short period gravity waves there is a tendency for a decreasing occurrence of NLC and for variable weak PMSE structures.